Author Topic: LEC 5101 QUIZ 5  (Read 463 times)

Lan Cheng

  • Jr. Member
  • **
  • Posts: 10
  • Karma: 9
    • View Profile
LEC 5101 QUIZ 5
« on: November 01, 2019, 02:00:17 PM »
Find the general solution of the given differential equation:

$y"+4y'+4y=t^{-2}e^{-2t},t>0.$

Let $y"+4y'+4y=0.$

$r^{2}+4r+4=0,r_{1}=-2=r_{2}.$

Thus,

$y_{c}(t)=C_{1}e^{-2t}+C_{2}te^{-2t}.$

$W=\begin{vmatrix}e^{-2t} & te^{-2t}\\
-2e^{-2t} & -2te^{-2t}+e^{-2t}
\end{vmatrix}=-2te^{4t}+e^{4t}+2te^{4t}=e^{4t}.$

$W_{1}=\begin{vmatrix}0 & te^{-2t}\\
1 & -2te^{-2t}+e^{-2t}
\end{vmatrix}=-te^{-2t}.$

$W_{2}=\begin{vmatrix}e^{-2t} & 0\\
-2e^{-2t} & 1
\end{vmatrix}=e^{-2t}.$

Let $\mu_{1}=\int\frac{W_{1}(t)g(t)}{W(t)}dt=\int\frac{-te^{-2t}\times t^{-2}e^{-2t}}{e^{4t}}dt=-ln(t). $

$\mu_{2}=\int\frac{W_{2}(t)g(t)}{W(t)}dt=\int\frac{e^{-2t}\times t^{-2}e^{-2t}}{e^{4t}}dt=-\frac{1}{t}.$

Therefore,

$y(t)=y_{1}(t)\mu_{1}+y_{2}(t)\mu_{2}+y_{c}(t)=-ln(t)e^{-2t}-e^{-2t}+C_{1}e^{-2t}+C_{2}te^{-2t}.$